Pertumbuhan dan Produksi Jagung Manis (Zea Mays L. Saccharata) dengan Aplikasi Pupuk Organik Cair Bonggol Pisang dan Pupuk Kandang Sapi - Natanael Ginting; Erlita Chaniago; Farida Hariani (Jurnal Agrofolium, 2024)
Liquid organic fertilizer has many advantages. This research aims to determine whether giving banana weevil POC and giving cow manure can increase the growth and production of sweet corn (Zea mays L. sacharata) and their interactions.This research used a Randomized Block Factorial Design with 2 factors studied and 3 replications where the first factor was the administration of banana weevil POC (P) which consisted of 3 levels, namely P1 = 100 ml liters of water-1 plot-1, P1 = 200 ml liters of water -1 plot-1, P2 = 300 ml liter of air-1 plot-1. The second factor of giving cow manure (S) consists of 4 levels, namely S0 = no treatment (control), S1 = 2 kg plot-1, S2 = 4 kg plot-1, and S3 = 6 kg plot-1. The parameters observed were plant height (cm), weight of husked cobs per sample (g), and husked cob weight per plot (g).The research results showed that giving POC banana weevils had no significant effect on the parameters of plant height, weight of husked cobs per sample, and husked cob weight per plot. The application of cow manure had a very significant effect on the parameters of plant height, weight of husked cobs per sample and husked cob weight per plot. The interaction of the two fertilizer treatments had no significant effect on all observed parameters.